Кольорове зображення як особливий об’єкт дослідження - Рихтік, А. Б. (ХНУРЕ, 2023)
The choice of color image processing technology is primarily determined by the tasks that need to be solved. However, it is important to obtain additional information for image analysis. This can be done by considering different color spaces and their components. Further, after processing different components of the color space, it is necessary to convolve such results. This will improve the quality of color image processing and improve the perception of the analysis results.
Keywords: кольорове зображення; особливий об’єкт дослідження